Limit Distributions of Ordered Random Variables in Mixture of Two Gaussian Sequences - H. M. Barakat; M. H. Dwes (Journal of Mathematics)
In this paper, we study the limit distributions of extreme, intermediate, and central order statistics, as well as record values, of the mixture of two stationary Gaussian sequences under equicorrelated setup.